Hillbilly elegy : a memoir of a family and culture in crisis - Vance, J. D. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
Vance, a former marine and Yale Law School graduate, provides an account of growing up in a poor Rust Belt town that offers a broader, probing look at the struggles of America's white working class. The decline of this group, a demographic of our country that has been slowly disintegrating over forty years, has been reported on with growing frequency and alarm. J. D. Vance tells the true story of what a social, regional, and class decline feels like when you were born with it hung around your neck. The Vance family story begins hopefully in postwar America. J. D.'s grandparents were "dirt poor and in love," and moved north from Kentucky's Appalachia region to Ohio in the hopes of escaping the dreadful poverty around them. They raised a middle-class family, and eventually their grandchild (the author) would graduate from Yale Law School, a conventional marker of their success in achieving generational upward mobility. But as the family saga of Hillbilly Elegy plays out, we learn that this is only the short, superficial version. Vance's grandparents, aunt, uncle, sister, and, most of all, his mother, struggled profoundly with the demands of their new middle-class life, and were never able to fully escape the legacy of abuse, alcoholism, poverty, and trauma so characteristic of their part of America
Includes bibliographical references (pages 263-264)
Keywords: Vance, J. D; Vance, J. D. -- Family; Working class whites -- United States -- Biography; Working class whites -- United States -- Social conditions; Mountain people -- Kentucky -- Social conditions; Social mobility -- United States -- Case studies; Appalachian Region -- Economic conditions; Autobiographies